WHERE THE VERY HUNGRY CATERPILLAR - Carle, Eric (PENGUIN BOOKS LIMITED (UK), 2016)
This gorgeous new interactive format lets babies and toddlers learn all about colours, shapes, numbers and first words- with a special sparkly surprise at the end! With lots of fun textures to explore, it's the perfect book to help with the development of all little readers everywhere.